Teslet-model: The application of web-based for measurement of student learning achievement on math subject - Wirasasmita, Rasyid Hardi; Hayati, Nila; Alpian, Mimi; Uska, Muhammad Zamroni (AIP conference proceedings, 2024)
The purpose of this study is to find out the application of web-based testlet-model in the measurement of achievement of mathematics students at the junior high school level. This research is a quality descriptive study, data sources in stinging come from teachers and learners from five schools. Data collection techniques are carried out using interview and observation techniques. Data analysis techniques are performed with interactive techniques. Based on the results of data analysis conducted, it is known that most teachers and first-time of new students use testlet-model let alone web-based ones. implementation of teslet model is located at the level of the user and has different access. The intended user level is central admin, school admin, teacher, and student. Constraints in the examination of this web-based testlet-model on network problems and students’ ability to operate computers. This application helps teachers to know the level of understanding and can minimize the number of students doing guesses so that they can describe the actual ability of students.